Caracterização fenotípica dos sistemas de grupos sanguíneos ABO, MNS e Duffy e genotipagem do grupo Duffy nos indivíduos de áreas endêmicas de malária no Brasil - Cavasini, Carlos Eugênio (2007)
The innate resistance to malarial infections in humans has been attributed to blood group polymorphism. We compared the phenotypic frequencies of ABO, MNS and Duffy and genotypic Duffy were phenotyped by serological tests and Duffy group genotyping by PCR / RFLP. For the analyzes of significance and to obtain the independence between the proportions, Fisher's exact test was used, with significance level of 0.05%. Results: Our results showed no correlation between ABO phenotypes and malarial infections in the studied areas. A significant association was observed between blood donors and malaria patients with the S + s + and S + s- phenotypes. In distinct areas, a significant correlation was detected between these two groups of individuals with some Duffy phenotypes. Discussion and Conclusions: We identified two individuals homozygous for the P. vivax-infected FYB-33 (Duffy negative) allele, whose genetic variants of this parasite were VK210 and or P. vivax-like. Duffy genotyping results in the study groups showed high frequencies of FYA / FYB genotype, followed by FYA, FYB, and FYA / FYB-33 and FYB / FYB-33 heterozygotes. Low frequencies of the FYA / FY *, FYB / FY *, FY * / FY * and FY * FYB33 genotypes were detected. Duffy negative genotype (FYB-33 / FYB-33) was found in both blood donor and malarial patients. No individual had the FY * / FYB-33 genotype. Our data suggest that individuals with the FYA / FYB genotype are more susceptible to P. vivax malaria. The presence of the FYB-33 allele may be a selective advantage in the population, which may reduce the rate of infection by that Plasmodium in that region.